Ornamental motives of modern design practices - O. D. Rykhlitska,; O. I. Kosyk, (Ukrainian Cultural Studies, 2021)
The article analyzes modern design practices based on symbolic and ornamental motives of folk art and their modern actualization in ethno-artistic areas, reflecting the relationship of traditional aspects with innovative, symbolic translation of cultural experience in time and space, creating symbolic value images, enhancing emotional environment and creating new narratives. Symbols, as the basis of the existence of the people, reflect the ethno-national aspects of culture, is an opportunity to find yourself at the level of relationship with your people, your nation, traditions.The appeal to archetypes is a special methodological perspective in which the meaning of the future is created due to the transformation of the past into a symbol. What is relevant in modern Ukrainian realities is that the whole cultural paradigm is being reconsidered and new ways of national identification are being sought. Embroidery is marked by a special color and incredible ornamentation, complex performance technique, which is reflected in the symbols of sociocultural practices, immersing in the depths of traditional norms and values that encourage to feel, assimilate, preserve and transmit.In modern domestic discourse, design practices are thought of as aimed at transforming the cultural environment into the integrity of cultural and natural components. They serve as a basis for forming an idea of the world and building harmonious relationships with the world. And the use of symbols-amulets and a certain emotional color is a special process of self-identification and the foundation for the revival of national culture and spiritual values, seeing their own place in the global cultural and artistic space. Therefore, the use of ornamental symbols in design practice is the basis for the revival of national culture and spiritual values and the formation of a new promising direction of Ukrainian design. Among the spiritual heritage of Ukraine with its color and incredible ornamentation, complex technique is embroidery, which is reflected in the symbols-codes of modern socio-cultural practices.
Keywords: symbol, ornament, design, design practice, ethnodesign, folk art, graphic design, landscape design, national identification